Meningkatkan Kecerdasan Interpersonal Melalui Kegiatan Tari Islami Di PAUD Riyadhul Badiah Temp[uran - Masrifah, Imas; Aisyah, Dewi Siti; Putri, Feronica Eka (Peneliti.net, 2025)
Islamic dance activities in group B PAUD Riyadhul Badiah Tempuran aim to improve interpersonal intelligence in children aged 5-6 years. The classroom action research (CAR) method using the Kemmis and Mc Taggart model was used in this research. This study was conducted in two cycles with cycle I including 6 meetings, and cycle II including 3 meetings. 10 children from group B PAUD Riyadhul Badiah Tempuran were the subjects of this research. Observation, interviews and documentation are data collection techniques. The study’s finding indicate that Islamic dancing can help group B kids at PAUD Riyadhul Badiah Tempuran become more interpersonally intelligent. This is demonstrated by increase in data from pre-action of 30.59%, after action in cycle I of 58.24%, and an increase after action in cycle II of 85.29%.